Laws and Ordinances for the Government of the Municipal Corporation of the City of Williamsport, Pa., at 141, An ordinance prescribing the rules and regulations for the government and protection of Brandon Park, § 21 (1891) - (:unkn) unknown (General Publisher, 1891)
Prohibited carry of fire-arms, shooting in the park, discharging fire-works, throwing stones, or throwing missiles within the limits of Brandon Park
--
Keywords: CARRY - CERTAIN PUBLIC PLACES